Modal dispersion characteristics of an elliptical optical waveguide having one-fourth of the cladding region loaded with highly conducting material - Joshi M.; Singh V.; Prasad B.; Ojha S.P. (My University, 2025)
In this letter, a theoretical analysis has been conducted to obtain the modal dispersion characteristics of an elliptical optical waveguide having one-fourth of the cladding region loaded with metal. Using Goell's point matching method under the weak guidance condition, the modal eigenvalue equation has been deduced numerically. From this equation dispersion curves are obtained and plotted.